Pedagogical and decolonial affordances of group portfolio assessments for learning in South African universities - Fouche, Ilse; Andrews, Grant; Dison, Laura; Prozesky, Maria (Critical Studies in Teaching and Learning, 2023)
Our paper discusses our recent experiences with designing effective assessments for challenging local contexts by using group work portfolio projects. South African universities are experiencing ever-increasing student numbers, diverse student bodies which have different language and literacy skill levels, and limited resources. Simultaneously, the need to decolonise university curricula and teaching and learning practices is being actively investigated across South Africa. In this paper, we discuss preliminary steps we have taken towards achieving this broader transformative agenda in the context of the massification of education, namely designing effective and decolonial assessments that support epistemological access and academic success, while at the same time challenging what counts as ‘powerful knowledge’ (Young and Muller, 2013) in the classroom. We argue that effective decolonial knowledge practices and deep critical engagement can be achieved by using group work portfolio tasks that align with assessment for learning principles (Carless, 2015). Using a design-based research approach, we describe three courses across two universities which have implemented portfolio-type group assessments. The preliminary findings suggest that group projects can yield rich and productive assessment for learning outcomes in large classes. In addition, portfolio projects that purposely interrogate diverse perspectives, knowledges and experiences can harness the diversity of groups to work towards decolonising the classroom.